PERAN DISIPLIN BELAJAR DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SD 1 DERSALAM KUDUS - Hajeng Laili Rohmah; Khamdun; Ahmad Bakhruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The reality in the fourth grade of SD 1 Dersalam Kudus indicates that some students still have low learning motivation, as reflected by their lack of enthusiasm, limited participation in classroom activities, and tendency to delay completing assignments. This study aims to describe the implementation of learning discipline and analyze its role in improving students’ learning motivation. A descriptive qualitative method was employed, with learning discipline as the main focus and learning motivation as the related aspect. The participants were fourth-grade students and teachers at SD 1 Dersalam Kudus. Data were collected through interviews, observations, and documentation using interview guides, observation sheets, and supporting documents. The findings show that learning discipline plays an important role in enhancing students’ motivation. Habits such as punctuality, compliance with school rules, responsibility in completing assignments, and effective study time management encourage greater enthusiasm, participation, and focus during learning. These practices also foster students’ awareness of achieving better learning outcomes. Overall, the implementation of learning discipline creates a more conducive learning environment and contributes to increased student learning motivation at SD 1 Dersalam Kudus.